Basic Regularities of Assessing Ore Pulp Parameters in Gravity Settling of Solid Phase Particles Based on Ultrasonic Measurements - Vladimir MORKUN; Natalia MORKUN; Vitalii TRON; Svitlana HRYSHCHENKO; Oleksandra SERDIUK; Irina DOTSENKO (Archives of Acoustics)
The article describes the method of controlling the recovered grade based on measuring the intensity of volume ultrasonic oscillations and Lamb waves covering a fixed distance through the test medium and on a metal plate contacting the test medium at various time points of deliberate motion of ground materials. The authors suggest a method of determining density of ground ore particles in the pulp periodically after isolating the pulp flow in the vertical part of the measuring vessel based on measuring attenuation change values in Lamb waves covering a fixed distance on a plate contacting the medium under study and high frequency volume ultrasonic oscillations that have come through it within a certain time period. There are given dependencies of amplitudes of measuring channels based on volume ultrasonic oscillations and surface Lamb waves, size distribution according to solid phase pulp particles for various types of ores under study, a set of curves for determining the recovered grade with regard to various types of ores under study.